Modeling environmental performance and economic development - Duasa, Jarita; Rafia, Afroz (International Association of Computer Science and Information Technology (I A C S I T), 2013)
The paper attempts to explore the contribution of economic development, population size or population density as well as the landlocked characteristic of the countries on the environmental performance using cross-sectional data of countries in the world listed by the United Nation (UN). The methods adopted in the present study are Ordinary Least Square (OLS) method and Generalized Method of Moments (GMM). Overall, using Environmental Performance Indicator (EPI) 2010 as a measurement of the effectiveness of national environmental protection effort, the present study finds that economic development/performance positively contributes to the countries’ environmental performance. On the other hand, population size gives negative impact on the environmental performance of the countries.